Confession and criminal justice in late medieval Italy Siena, 1260-1330 - Zanetti Domingues, Lidia Luisa 1990- (Oxford Oxford University Press USA - OSO, 2021)
This monograph provides an in-depth comparison of lay and religious sources produced in Siena (1260-1330) on criminal justice, conflict, and violence.
Cover -- Confession and Criminal Justice in Late Medieval Italy: Siena, 1260-1330 -- Copyright -- Acknowledgements -- Contents -- Note on Dates and Translations -- Abbreviations -- Introduction -- 1. Why do we React to Violence the Way we do? -- 2. Lessons on Violent Crime from Medieval Studies -- 3. Siena, 1260-1330: An Outline of its Political, Social, and Religious Context -- 4. Sources and Themes -- 1: Competing Models for Approaching Violence and Conflict and their Points of Contact -- 1. A Penitential Conception of Criminal Justice -- 2. What is a Model, or a Discourse, of Criminal Justice? -- 3. Similarities and Differences Between Models -- 4. Individuals and Community: Shame, Guilt, and 'Shame-Guilt' -- 5. Who were the Bearers of these Different Models in Late Medieval Siena? -- 2: Emotions, Virtues, and Vices in the Sienese Reflection on Violence and its Remedies -- 1. The History of Emotions, Virtues, and Vices -- 2. 'Good' and 'Bad' Emotions in Thirteenth-Century Religious Thought -- 3. The Penitential Model of Civic Virtues: Humility, Patience, Mercy -- 3: Models of Emotionality in Action in Religious and Lay Sources on Criminal Justice -- 1. Humility and Emotional Control -- 2. Patience and Humility versus Anger and Pride -- 3. Mercy as a 'Script' for Dispute Settlement -- 4. The Strategic Role of Virtues -- 5. To what Extent was this Model Influential on the Laity? -- 4: Defining the Complex Relationship between Mercy, Justice, and Revenge -- 1. Theological Theories of Redemption and Atonement and Reforms of Criminal Justice -- 2. The Nature of Divine Justice in Sienese Sermons -- 3. The Dangers of Judging: Aims and Problems of Human Justice in Sienese Sermons -- 5: Communal Legislation and the Pursuit of Divine Justice -- 1. The System of Criminal Justice in Siena and its Functions -- 2. Was Vendetta Legal in Medieval Siena?.
Description based on publisher supplied metadata and other sources
Keywords: Criminal justice, Administration of-Italy-Siena-History-To 1500; Crime-Italy-Siena-History-To 1500; Confession-History-To 1500; Siena (Italy)-History-Rule of the Nine, 1287-1355; Electronic books